Formation of social and legal competence of future social teachers (Journal of Educational Sciences, 2023)
Complex and contradictory processes of change in all spheres of public life in our country place special demands on the quality of professional competence of specialists. The article analyzes the process of solving theoretical and applied problems related to the task of developing the professional and legal competence of social educators. In accordance with the purpose of the study, in accordance with the direction of changes taking place in the world, in society, the main directions for increasing the professional legal competence of a social teacher and analyzing the professional qualifications of a social teacher are: done.   The qualification characteristics of a social teacher, including a list of job responsibilities, determine the main types of assistance provided by a social teacher to a child, where social and legal competence is aimed at protecting the rights of adolescents and children and promoting the implementation of legal norms. The guarantees of various categories of children and the legal education of the younger generation were studied. To effectively implement these types of activities, social educators need to know the legal documents in the field of children’s rights, be able to use them in their professional activities, and know the socio-legal and socio-economic foundations of their activities. educational institutions providing assistance to children and their families; The pedagogical conditions that ensure the effectiveness of its implementation are described. An experimental study was conducted in which 47 undergraduate students of the L. Gumilev Eurasian National University took part. The formative experiment included 4 stages of development of socio-legal competence (informational-cognitive, value-oriented, regulatory and communicative stages). The dynamics of changes in the social and legal competence of a social teacher are shown.Key words: social teacher, socio-legal competence, professional competence.